2021
DOI: 10.21037/atm-21-409
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the clearance of HBsAg and the remodeling of B cell subsets in CHB patients treated with Peg-IFN-α

Abstract: Background: The seroconversion of the hepatitis B antigen is the ideal outcome for long-acting interferon-pegylated interferon-α (Peg-IFN-α) treatment among patients with chronic hepatitis B (CHB). B-cell response plays an important role in the process of hepatitis B antigen clearance, but the specific mechanism by which B-cell improve hepatitis B virus (HBV) is still unclear.Methods: A total of 103 CHB patients participated in this study. The patients received 24 weeks of Peg-IFN-α treatment. Flow cytometry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The results of similar studies showed that the anti-HBs-seroconversion rates post-hepatitis B vaccination ranged from 81.8 to 100% in individuals with HBsAg seroclearance after IFNα-based therapy, compared to 0–36.4% in unvaccinated individuals [ 9 , 10 , 15 ]. Patients with CHB who were treated with Peg-IFNα for 24 weeks showed significant increases in memory B and plasma cells, relative to baseline levels [ 17 ]. In contrast, untreated patients with CHB had difficulty producing anti-HBs even when administered multiple hepatitis B-vaccine doses, which may relate to severe B cell dysfunction in patients with CHB [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of similar studies showed that the anti-HBs-seroconversion rates post-hepatitis B vaccination ranged from 81.8 to 100% in individuals with HBsAg seroclearance after IFNα-based therapy, compared to 0–36.4% in unvaccinated individuals [ 9 , 10 , 15 ]. Patients with CHB who were treated with Peg-IFNα for 24 weeks showed significant increases in memory B and plasma cells, relative to baseline levels [ 17 ]. In contrast, untreated patients with CHB had difficulty producing anti-HBs even when administered multiple hepatitis B-vaccine doses, which may relate to severe B cell dysfunction in patients with CHB [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the number of Breg cells were not significant in the non-vaccinated group. Previous reports revealed that, overall, Breg cells increased significantly during the early stage of Peg-IFNα treatment (12–24 weeks) [ 17 , 33 ]. However, Fu et al showed that with extended Peg-IFNα treatment, the proportion of Breg cells gradually decreased, which correlated significantly with a higher HBeAg-seroconversion rate and higher IgG secretion [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…67 The study of B-cell subsets in peripheral blood mononuclear cells from a subset of Everest project patients found that B-cell subsets were reformed after Peg-IFNα treatment in CHB patients and were associated with HBsAg clearance. 68 sCD163 has also been shown to be a useful serum marker of CHB and can be used as a predictor of HBsAg clearance. 69 The results of one study showed that the proportion of baseline mMD-SCs and CD4+ Treg cells in HBeAg-negative CHB patients was REVIEW significantly higher than that healthy people, with the highest proportion in patients who did not achieve HBsAg clearance.…”
Section: Preferred Population and Clinical Indicators That Predict Hb...mentioning
confidence: 99%
“…They are effective for suppressing HBV replication, but not for silencing or eliminating circular DNA; hence, they hardly reduce HBsAg levels, and the overall therapeutic effect is unsatisfactory. Moreover, long-term NUCs antiviral therapy has potential drug-related side effects, psychological burden, relapse from drug withdrawal, and risk of virus resistance [ 17 19 ]. IFN exerts direct antiviral and immunoregulatory activities, inhibiting HBV DNA and RNA replication and eliminating virus-infected cells by enhancing the activity of immune cells, including that of cytotoxic T cells and antigen presenting cells, which in turn inhibit viral protein synthesis and the maturation and egress of virus particles.…”
Section: Introductionmentioning
confidence: 99%